Intimate Partner Violence and Women’s Mental Health: The Mediating Role of Coping Strategies Among Women Seeking Help From the Police - Mengo, Cecilia (Journal of interpersonal violence, 2021)
Many variables explain the link between intimate partner violence (IPV) and its impact on women’s mental health. This proposition is mostly from samples drawn from battered women’s shelters, batterer intervention programs (BIPs), emergency rooms, and medical clinics. We know little about the psychological well-being of women who report abuse to police departments. This study used data from case records of women who experience IPV and sought help from a city police station located in the southwest United States. These case records were examined to identify how sociodemographic characteristics of age, ethnicity, marital status, financial dependence, resources of social support, and coping strategies related with type and number of IPV incidents as well as mental health symptoms. The sample consisted of 154 women, majority of whom experienced physical violence (70.1%), sexual violence (9.1%), emotional violence/stalking (14.9%), and combined, that is, reporting more than one (5.8%). Approximately 67.5% of the women reported some mental health symptoms. Social support and coping strategies significantly distinguished women’s experience of mental health symptoms. Unexpectedly, the current data indicate that women who scored higher in perceived social support significantly reported more mental health symptoms. Coping strategies mediated the relationship between IPV and mental health symptoms. The findings suggest that availability of coping resources may mitigate repeated IPV and modify the impact of mental health. In discussing prevention and intervention efforts with women who have experienced or are at risk of experiencing IPV, practitioners can help women employ empowering coping strategies that are built on their resilience. In addition, mental health professionals working with the police, especially in community policing setting, can achieve promising outcomes for women experiencing violence.